ANALISIS PENGARUH CITRA MEREK, PROMOSI, DAN KUALITAS PRODUK TERHADAP KEPUASAN KONSUMEN PADA PT BUSANA HAJI INDONESIA (AL-MI’A) JAKARTA - Darwati, Ani (JEBI | Jurnal Ekonomi Bisnis Indonesia, 2024)
The purpose of this study is to determine the effect analysis of brand image, promotion, and product quality toward consumer satisfaction at PT Busana Haji Indonesia (Al-Mi’a). The research method uses field surveys. Based on the results of the study obtained the following conclusions:Partial test results for brand image variables with a statistic value of tcount>ttable (2.103 > 1.984) and a probability value of 0.038 < 0.05, then Ho is rejected, means that there is a significant influence of the brand image variables on customer satisfaction.Partial test results for promotional variables with a statistic value of tcount<ttable (1.511 <1.984) and a probability value of 0.134> 0.05, then Ho is accepted means that there is no significant influence of the promotion variables on customer satisfaction.Partial test results for product quality variables with a statistic value of tcount>ttable (2.290 > 1.984) and a probability value of 0.024 < 0.05, then Ho is rejected means that there is a significant influence of the product quality variable on customer satisfaction.Simultaneous test results with a value of Fcount>Ftable (5.141 > 2.699), then Ho is rejected and Ha is accepted which means that there are significant simultaneous influence (together) of the variables of brand image, promotion, and product quality together the same(simultaneous) has a significant effect on the dependent variable namely customer satisfaction.The magnitude of the correlation coefficient (R) is 0.372, which means there is a weak correlation between the independent variables consisting of brand image, promotion, and product quality with the dependent variable namely customer satisfaction.The amount of adjusted coefficient of determination (adjusted R2) is 0.112, which means that the independent variables consisting of brand image, promotion, and product quality can contribute an influence of 11.2% to customer satisfaction while the remaining 88.8% is explained by other factors not included in the model.